(untitled) (REMUNOM, 2025)
This article deals with the institute of Judicial and Extrajudicial Recovery in Brazil, such institute is established in the Brazilian legal system, more specifically in Law No. 11.101, of February 9, 2005. This Law came to regulate the judicial recovery, the extrajudicial recovery and the bankruptcy of the entrepreneur and the business society, considered a great advance for the Brazilian legal system, since it brought greater security and dynamism to the entire procedure, especially for the companies and for the others involved. As the article progresses, the advantages of the extrajudicial recovery will be demonstrated, with practical examples, as this is a faster way and capable of solving the problem of the insolvent debtor. The methodology adopted was exploratory, with the use of the bankruptcy and recovery law, the Civil Code, case law, doctrinal works, as well as websites with legal content. The choice of the theme is justified given the relevance of judicial and extrajudicial recovery for the entrepreneur and the business society, as well as a greater understanding of the bankruptcy procedure and the possibility of its conversion to the recovery so desired by the entrepreneur in the face of the crisis in the company.